HUBUNGAN MOTIVASI BELAJAR DENGAN TINGKAT PROKASTINASI AKADEMIK MAHASISWA STATISTIKA UII - Nidzar Zulmi Dwisyahputra; Putri Stania Adhiana; Anisa Srikandi; Edy Widodo (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2021)
Currently, with the condition of lectures online or through online classes which are more to demand students to be proactive in learning activities and are expected to get assignments outside of class hours. However, in reality the task becomes a burden for students and many of them feel bored and tired. Boredom and tiredness cause students to stay away from tasks that must be completed and tend to procrastinate. Procrastination which is usually carried out in an academic environment is also known as academic procrastination because what is postponed is tasks that are in the academic area. In fact, one of the targets of the Statistics study program at the Islamic University of Indonesia is to obtain good achievements for graduates of the Indonesian Islamic University while in the outside world. This shows that Statistics Indonesia Islamic University expects its students to have high enthusiasm in learning and studying. Therefore, the researcher wants to prove whether there is a relationship between learning motivation and the procrastination level of 2019 Islamic University of Indonesia statistics students by using correlational quantitative methods. So that we get the results that in fact there is no significant correlation between the procrastination variable and the learning motivation variable